Thermoelastic stress analysis of fatigue cracks subject to overloads - PATKI, A. S.; PATTERSON, E. A. (Fatigue & fracture of engineering materials & structures, 2010)
ABSTRACT In this study, the effects of plasticity‐induced crack closure and overloads were investigated using thermoelastic stress analysis (TSA) in aluminum alloy 2024. The amplitude of the stress intensity factors were evaluated during crack growth by fitting a Muskhelishvili‐type description of the crack tip stress fields to the TSA data using the multipoint overdeterministic method. A new method to directly measure the extent of the crack tip plastic zone is proposed based on the phase difference between the TSA and forcing signals. The presence of crack tip plasticity was clearly identified and correlated with changes in the stress intensity factor values obtained from the TSA data both during constant amplitude loading as well as single and multiple overloads. Immediately post‐overload the plastic zone increased in size by up to 50% whereas the amplitude of the stress intensity factor and the crack growth rate decreased until the crack grew through the plastic region created by the overload when the pre‐overload value of the crack growth was re‐attained. The experimental data of mode I stress intensity factor, crack growth rate and radius of crack tip plastic zone obtained from thermoelastic data in the region affected by the overload were used to estimate the exponent in the Wheeler crack growth model which was found to be a function of percentage overload and the number of cycles of overload.